2021
DOI: 10.3390/molecules26164927
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Amidinourea Derivatives against Herpes Simplex Viruses

Abstract: Current therapy against herpes simplex viruses (HSV) relies on the use of a few nucleoside antivirals such as acyclovir, famciclovir and valacyclovir. However, the current drugs are ineffective against latent and drug-resistant HSV infections. A series of amidinourea compounds, designed as analogues of the antiviral drug moroxydine, has been synthesized and evaluated as potential non-nucleoside anti-HSV agents. Three compounds showed micromolar activity against HSV-1 and low cytotoxicity, turning to be promisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…It was also shown that the tested substances have a different mechanism of action than the nucleotide analogues. They act on the early stages of virus replication [ 151 ]. MBZM-N-IBT1-[(2-methyl benzimidazole-1-yl) methyl]-2-oxo-indolin-3-ylidene] amino] thiourea is also in preclinical testing.…”
Section: Compounds With Potential Use In the Treatment Of Herpesvirus...mentioning
confidence: 99%
“…It was also shown that the tested substances have a different mechanism of action than the nucleotide analogues. They act on the early stages of virus replication [ 151 ]. MBZM-N-IBT1-[(2-methyl benzimidazole-1-yl) methyl]-2-oxo-indolin-3-ylidene] amino] thiourea is also in preclinical testing.…”
Section: Compounds With Potential Use In the Treatment Of Herpesvirus...mentioning
confidence: 99%
“…Within this time frame, there were two (1.46%) studies in 2015 [ 6 , 7 ], 15 (10.95%) studies in 2016 [ 1 , 3 , 8 - 20 ], 19 (13.87%) studies in 2017 [ 21 - 39 ], 27 (19.71%) studies in 2018 [ 40 - 64 ], 23 (16.79%) studies in 2019 [ 2 , 65 - 86 ], 24 (17.52%) studies in 2020 [ 87 - 110 ], and 27 (19.70%) studies in 2021 [ 111 - 137 ]. Regarding the type of studies reviewed, 121 (88.32%) studies included in vitro elements [ 2 , 3 , 6 - 12 , 14 - 20 , 23 - 26 , 28 - 42 , 44 - 47 , 49 - 56 , 58 - 64 , 66 , 68 - 72 , 74 - 77 , 79 , 80 , 82 - 87 , 89 - 118 , 120 , 122 - 133 , 135 - 139 ] and 23 (16.79%) in vivo [ 2 , 13 , 15 , 18 , 22 , 25 , 27 , 28 , 37 , 43 , 48 , 56 , 62 , 67 , 73 , 78 , 81 , 100 , …”
Section: Reviewmentioning
confidence: 99%
“…Sample size was extremely variable and unable to be compared due to the differences in study designs. In terms of sample characteristics, 99 (72.26%) studies used Vero cells [ 2 , 3 , 6 , 8 - 10 , 14 - 20 , 23 , 25 , 26 , 28 , 30 - 34 , 36 , 39 - 42 , 44 - 47 , 50 , 51 , 53 - 56 , 58 - 64 , 66 - 70 , 72 , 74 , 76 , 77 , 79 , 82 , 83 , 85 - 87 , 89 - 95 , 97 - 108 , 111 - 113 , 115 - 118 , 120 , 122 , 123 , 125 - 130 , 132 , 133 , 135 , 137 , 138 ], 41 (29.93%) used human cell lines [ 7 , 11 , 12 , 16 , 19 , 24 , 29 , 31 , 36 , 38 , 47 , 49 , 52 - 56 , 61 , 62 , 67 ,…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations